Does Board Gender Diversity really increase Innovation Intensity? Evidence from S&P500 Firms - PENG, YUE (2020)
This study examines whether corporate board gender diversity has positive effect on firm innovation intensity, using a sample of S&P 500 firms from 2010 to 2019. It finds that all results of three panel data models, including Pooled OLS model, Radom Effect (RE) model and Fixed Effect (FE) model, indicate an insignificant association between the gender diversity on boards and intensity of innovation. By conducting a series of tests, the FE model is chosen as the most appropriate model. However, after checking the influence within individual industries, adopting Instrumental Variable (IV) Approach to deal with endogeneity problems and considering the robustness test for lag effect, the percentage of female directors is still not statistically significant with R&D expenditure, R&D expenditure over the number of employees and R&D expenditure over sales. In general, the finding suggests that the board gender diversity does not significantly increase innovation intensity on the basis of this data-set.